2017
DOI: 10.14202/vetworld.2017.281-285
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of total mixed ration supplemented with exogenous fibrolytic enzymes for crossbred cows

Abstract: Aim:The study was conducted to evaluate the levels of exogenous fibrolytic enzymes (EFE) on in vitro digestibilities of dry matter (DM) and organic matter (OM), total gas production (TGP), metabolizable energy (ME) content, and microbial biomass production (MBP).Materials and Methods:The total mixed ration (TMR) was prepared using 30% each of sorghum hay and groundnut straw and 40% compound concentrate mixture to meet nutritional requirement of cow (500 kg) producing 12 kg fat corrected milk. The EFE was incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Meanwhile, feedstuffs having lower crude fiber generally has higher feed intake because the cell wall is thin thus can be penetrated by digestive latex (Riswandi et al, 2015). Rumen microorganism can synthesize and secresize cellulose enzyme β 1-4 which roles on hydrolyzing plant cell wall thus high crude fiber feedstuffs can be degraded into high quality feedstuffs (Lunagariya et al, 2017). Microorganism of synthesis up to 30-40 g/kg of digestible organic matter or equal to 187.5-250 g protein of microorganism/kg of digestible organic matter (Mayulu, 2014).…”
Section: Dry Matter and Organic Matter Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, feedstuffs having lower crude fiber generally has higher feed intake because the cell wall is thin thus can be penetrated by digestive latex (Riswandi et al, 2015). Rumen microorganism can synthesize and secresize cellulose enzyme β 1-4 which roles on hydrolyzing plant cell wall thus high crude fiber feedstuffs can be degraded into high quality feedstuffs (Lunagariya et al, 2017). Microorganism of synthesis up to 30-40 g/kg of digestible organic matter or equal to 187.5-250 g protein of microorganism/kg of digestible organic matter (Mayulu, 2014).…”
Section: Dry Matter and Organic Matter Digestibilitymentioning
confidence: 99%
“…A qualified feed is an important factor to fulfill livestock growth needs to achieve maximum beef production as well as to achieve a successful livestock enterprise (Yakin et al, 2012) so income of farmers increase. Ruminant is a livestock commodity that can utilize a low feedstuffs quality and high crude fiber and then digests into a qualified feeds (Lunagariya et al, 2017). feedstuffs used to formulate ration should contain adequate nutrient content (protein, carbohydrate, fat, mineral, vitamin and water) for sheep thus can produce optimum result.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropical and sub-tropical developing countries of the world, there is a wide and distinct difference between obtainable and needed livestock feeds. Ruminants in these areas are frequently fed highly lignified roughages and crop residues, which are low in available energy, nitrogen and minerals (Lunagariya et al, 2017). A large proportion of these plants compose of structural carbohydrate shielded by lignin, which is not easily degraded by rumen microbes (Sallam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The digestibility of dry and organic matter in this study is higher than those reported in previous studies. A study by Lunagariya et al (2017) on mixed diets enhanced with external additives showed that the fibrinolytic enzymes resulted in a dry matter digestibility of 63.03% and an organic matter digestibility of 63.62%. Aslamyah et al (2017) showed that seaweed fermentation using a combination of microorganisms produces dry matter and organic matter digestibility of 60.92 and 57.77%, respectively.…”
Section: The Role Of Mixed Microbes To Improve Dry Matter Digestibili...mentioning
confidence: 99%